“Postantonovism” as a Special Stage in Development of Tambov Village (1921 — Mid-1920s) - V. P. Nikolashin; P. V. Erin; E. V. Gatilow (Научный диалог)
The socio-political situation of the Tambov village in the last months of the Antonov uprising and in the period after its completion is studied. The conflict, which had formed by 1920, was not resolved and took the form of an armed struggle, created the conditions for the development of “social banditry”. By the second half of 1921, the village “recognized” the strength of the Bolsheviks, but still longed for freedom from harsh tax policies, mobilizations, etc. In 1923 there was a progressive “appeasement” of the peasantry. The development of “social banditry” into “criminal banditry” begins. The number of crimes “against the Soviet Republic and the order of government” is declining, and property crimes are beginning to predominate. This was due to the improvement in the socio-economic situation of the peasantry after the 1922 harvest. Several tens of thousands of Antonovites and their families, because of the death of relatives, because of their stay in concentration camps, because of conflict relations in their villages with their neighbors, felt the consequences of the uprising for a long time. At the other extreme were the families of the Bolsheviks and Soviet workers killed by the rebels, who found themselves in a difficult economic situation. Representatives of the opposing sides were in decline, the apotheosis of which was the famine of 1922. For the restoration of the destabilized local society, progressive steps were required on the part of the authorities.